2008
DOI: 10.1088/1367-2630/10/9/093021
|View full text |Cite
|
Sign up to set email alerts
|

Hyper-domains in exchange bias micro-stripe pattern

Abstract: A combination of experimental techniques, e.g. vector-MOKE magnetometry, Kerr microscopy and polarized neutron reflectometry, was applied to study the field induced evolution of the magnetization distribution over a periodic pattern of alternating exchange bias stripes. The lateral structure is imprinted into a continuous ferromagnetic/antiferromagnetic exchange-bias bi-layer via laterally selective exposure to He-ion irradiation in an applied field. This creates an alternating frozen-in interfacial exchange b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 30 publications
1
14
1
Order By: Relevance
“…Rippling is a phenomenon known to occur in Co films ( [16]) and leads to an alternating canting of moments within the small domains and with respect to the applied field direction. Here, due to coupling across neighbouring stripes larger areas with tilted magnetic moments may build up, similar to recent observations by polarized neutron reflectometry (PNR) on Co stripe arrays, which exhibit hyperdomains stretching over several stripes [8,17]. Surprisingly and in contrast to these previous studies, here a tilt of the magnetization vectors is observed in the MOKE data, whereas before this effect was only seen by PNR.…”
Section: Moke Magnetometrysupporting
confidence: 88%
“…Rippling is a phenomenon known to occur in Co films ( [16]) and leads to an alternating canting of moments within the small domains and with respect to the applied field direction. Here, due to coupling across neighbouring stripes larger areas with tilted magnetic moments may build up, similar to recent observations by polarized neutron reflectometry (PNR) on Co stripe arrays, which exhibit hyperdomains stretching over several stripes [8,17]. Surprisingly and in contrast to these previous studies, here a tilt of the magnetization vectors is observed in the MOKE data, whereas before this effect was only seen by PNR.…”
Section: Moke Magnetometrysupporting
confidence: 88%
“…The difference is that now lateral magnetization of domains is provided by Bloch DWs, with which magnetic moments are correlated in a number of neighboring walls but decaying at large distances. Therefore, corresponding large areas carrying mean magnetization can be also called hyperdomains, as was previously observed [73] in stripe-patterned films. If the number of DWs within hyperdomains is large, then the absolute value (but not direction) of magnetization in each of them is about the same.…”
Section: Appendix: Data Treatment For Pnr Analysismentioning
confidence: 57%
“…At the same time, in the demagnetized sample, the net magnetization was reduced by an additional 92%, which is associated with incoherent averaging over larger domains. This means that demagnetization predominantly occurs via formation of large domains [73] comprising Bloch DWs.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the astonishing development of nanofabrication techniques [5][6][7][8] in recent years has opened the door to a new strategy, the patterning of nanostructures, that allows the modification of the local magnetization distribution in a controlled way. Peculiar magnetic domain structures appear on thin film surfaces, such as quasidomains [9], or in nanostructured thin films, such as hyperdomains [10] or superdomains [11]. The relevant characteristic length scale for magnetic phenomena in thin films is the exchange length [9] …”
Section: Introductionmentioning
confidence: 99%